El pequeño escarabajo de la colmena Aethina tumida Murray, un problema importante que afecta las abejas melíferas - Calderón Fallas, Rafael Ángel (2006)
A new exotic honey bee pest was detected in The United States. This pest is caused by the small hive beetle Aethina tumida Murray (Coleoptera: Nitidulidae). Adults and larvae beetles inhabit bechives, qhere they have been observed causing significant damage. Adult beetles consume eggs and the beetle larvae eat brood, pollen, honey and heavily damage wax comb. The economic losses due to the negative effects caused by the small hive beetle include: time and labor to detec and control the beetles, and losses in honey production and pollination. Factors that attract beetles and encourage their rapid growth are weak colonies and colonies with a surplus or combs stored on them. Due to economic importance of the small hive beetle in the beekeeping industry in the United States and because of the posibility that this pest could arrive to Costa Rica by the importation pf infested colonies, this paper is presented.